Analisis Efek Tapak Lokal pada Lokasi Stasiun Seismik di Pulau Jawa: Sesar Prabu Dwi Sriyanto, Indri Ifantyana - Sesar Prabu Dwi Sriyanto Sesar Prabu Dwi Sriyanto; Indri Ifantyana Indri Ifantyana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
One of the specification of good seismic station placement is the seismic sensor which should be placed on the bedrock to minimize the wave amplification factor that affect to the earthquake magnitude calculation. In this study, we analyze the soil characteristics in the seismic sensor location at 22 seismic stations placed in Java island. Seismogram data, which is free from seismic noise, from each station were analyzed using Horizontal to Vertical Spectral Ratio (HVSR) method to get the value of the soil amplification factor (Ao) and the dominant period (Tdom). To determine the type of soil at the seismic station location, we used the dominant period (Tdom). The result, 36.4% are located on soft soil, 13.6% on the medium soil type, 22.7% on the hard soil type, and 27.27% lies in the soil class I, which is a rock. The 10 seismic stations has the amplification factor more than 2.0, with the highest value is 7.73 at CNJI station (Cianjur, West Java Province) and the lowest value is 0.89 at TNGI station (Tangerang, Banten Province). Not only the local site effect but the treatment of the sensor also affects the seismic wave amplification at the stations.